Pola Komunikasi Pustakawan dalam Mengatasi Perilaku Vandalisme di Perpustakaan Universitas Medan Area (UMA) - Aini Ananda, Mega; Anas Azhar, Anang; Fatra Deni, Indira (Comit: Communication, Information and Technology Journal, 2024)
This study aims to determine the communication patterns of librarians in overcoming vandalism behavior in the Medan Area University (UMA) library. And to find out the communication barriers of librarians in overcoming vandalism behavior in the Medan Area University (UMA) library. The theory used in this research is the librarian's interpersonal communication theory. This type of research uses a qualitative method with a descriptive approach. The results of this study can be seen that the communication relationship of librarians in overcoming the vandalism behavior is good and good, and they provide each other with feedback and assistance in overcoming the vandalism behavior. The form of communication that occurs between librarians at the Medan Area University Library is interpersonal communication, namely direct communication by means of face to face or not, the type of communication carried out at the Medan Area University Library is formal communication, usually holding meetings to discuss progress and problems in the library, communication characteristics at the Medan Area University Library, namely face to face communication, then messages can be conveyed through verbal and non-verbal communication symbols. different priorities and different opinions so that the message conveyed is not in accordance with what is expected. Keywords : Patterns of Communication, Librarian, Vandalism.